2016
DOI: 10.1371/journal.pone.0160603
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Phylogenetic Analysis of Human Bocaviruses 1-4 in Pediatric Patients with Various Infectious Diseases

Abstract: ObjectivesViral infections caused by human bocaviruses 1–4 (HBoV1-4) are more complicated than previously believed. A retrospective, large-scale study was undertaken to explore the prevalence of HBoV1-4 in pediatric patients with various infectious diseases and delineate their phylogenetic characteristics.MethodsClinical samples from four specimen types, including 4,941 respiratory, 2,239 cerebrospinal fluid (CSF), 2,619 serum, and 1,121 fecal specimens, collected from pediatric patients with various infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In major reports, HBoV is the most common infectious cause and after major viruses can result in acute respiratory infection in children under 3 years old [4,11,12]. The major reports, one of these reports is Calvo et al's study, in single infections and dual infections of HBoV state that HBoV was detected in 9.9% as a distinctive pathogen and 75% as co-infections with other viral agents [13].…”
Section: Discussionmentioning
confidence: 99%
“…In major reports, HBoV is the most common infectious cause and after major viruses can result in acute respiratory infection in children under 3 years old [4,11,12]. The major reports, one of these reports is Calvo et al's study, in single infections and dual infections of HBoV state that HBoV was detected in 9.9% as a distinctive pathogen and 75% as co-infections with other viral agents [13].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009–2010, three additional HBoV genotypes (HBoV2–4) were reported [ 7 13 ], inspiring interest in the role of HBoVs in children. A growing number of studies have subsequently shown that HBoV is frequently detected in the feces of children with acute gastroenteritis [ 14 16 ]. Some case-control studies reported that HBoV is just a bystander in acute gastroenteritis, but that finding disagrees with the results of other studies on this topic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%